Pengembangan Interactive Book Berbantuan Aplikasi Lumi Education pada Materi Ekologi dan Keanekaragaman Hayati Indonesia sebagai Media Digital Peserta Didik Fase D Kurikulum Merdeka - Muhammad Zahki; Muhammad Nasir (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to develop an interactive book assisted by the Lumi Education application as a digital learning medium for ecology and biodiversity materials targeting Phase D students within the Merdeka Curriculum framework. The development employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The validation process involved two expert validators who assessed four primary aspects: design, pedagogy, content, and technical quality. Validation instruments used a 1–5 Likert scale, and media feasibility was measured using Aiken's V formula. Validation results show that the average Aiken's V value for design was 0.76, pedagogy 0.83, content 0.76, and technical aspects 0.68. The overall average Aiken's V was 0.76, categorized as valid. These findings indicate that the developed interactive book is feasible for use as a digital learning medium. The media was designed to facilitate active, self-directed, and digitally literate learning, in line with the Merdeka Belajar philosophy. Future research is recommended to test media effectiveness on a broader population and to integrate gamification features to enhance student motivation.